INTERAKSI POLITIK BIROKRAT DAN PETAHANA DI TIMOR TENGAH UTARA (TTU) DALAM PILKADA 2010 - , DIAN FESTIANTO, S.Ip; , Dr. rer. pol. Mada Sukmajati, S.Ip., MPP. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to describe the political interaction bureaucrats with incumbent at TTU mutually politicizing with focus on policy toward local election in 2010. This study was conducted with a case study approach descriptive analytical to the aim of building a theory based on the phenomenon of daily politics and put the actor as the unit of analysis. The collection of primary data through interviews with bureaucrats, successful teams, communities, and local politicians are using the interview guidelines, the snowball sampling technique to determine the informant. Observations were also made to understand the political meaning. Researcher also puts the local political actors as the key informant. Secondary data were also collected in the form of a public document as supporting research data, while data processing using a triangulation method. The results showed that the relationship bureaucrats with incumbent are reciprocal, dynamic and tend to be transactional, because each actor tried to realize self-interest involving political intrigue. Incumbent networks utilize, budget and bureaucratic authority as a political means to maintain power the incumbent for next period. On the other side, bureaucrats utilizing the power of incumbent as political backrest positions to improve the career bureaucrats. This relation has implications for the formation of political alliances in the internal bureaucracy in the form of a successful team based on similarity of pragmatism and ethnic identity, restructuring the bureaucracy are loaded with political interests bureaucrats and incumbent and duplication vested interests of bureaucrats and incumbent in the form of a quarry policy manganese products. Thus, the study found a new political phenomenon that is different from the concept of Halevy (2011), Geddes (1994) and Downs (1965) concerning the relation of politics and bureaucracy. Besides that, it turns rational choice approach has limitations in explaining local political rationality TTU is located in phase between identity politics and rational choice. This theoretical disparity be contributing to political academics who intend to conduct similar studies in order to enrich the rational choice theory, while in practice can add references to political interaction bureaucrats with incumbent in momentum local elections elsewhere.